Risks of developing unstable angina in female smokers - T. M. Solomenchuk; A. O. Bedzai; V. V. Protsko; V. L. Lutska (Zaporožskij Medicinskij Žurnal)
The aim of the study: to determine the prevalence, interrelation and prognostic value of the major risk factors (RF) of unstable angina (UA) in women, depending on smoking habits.